Croton sertanejus, a new species from Seasonally Dry Tropical Forest in Brazil, and redescription of C. echioides (Euphorbiaceae) - Sodré, Rodolfo Carneiro; da Silva, Marcos José (European Journal of Taxonomy, 2022)
During a taxonomic study of the species of Croton sect. Adenophylli occurring in Brazil, approximately 140 collections usually identified as Croton echioides, C. rhamnifolius or C. rhamnifolioides caught our attention due to the distinct morphology of vegetative and reproductive organs. After the analysis of these collections, we concluded that they represent a new species, C. sertanejus Sodré & M.J.Silva sp. nov., which was also corroborated by an anatomical study of their leaves. This new species can be differentiated by pseudomonopodial branching, leaves with petioles up to 1.7 cm long, 4–6 subsessile nectary glands and indumentum of sessile trichomes on both surfaces. Detailed descriptions, including details of leaf anatomy, are provided for C. sertanejus sp. nov. and C. echioides, its closely related species. We also formalize the synonymization of C. kalkmannii under C. echioides and re-evaluate the typification of these names, in order to better clarify their taxonomic status.